2019
DOI: 10.3390/rs11030279
|View full text |Cite
|
Sign up to set email alerts
|

An Overall Evaluation of Water Transparency in Lake Malawi from MERIS Data

Abstract: Lake Malawi is an important water resource in Africa. However, there is no routine monitoring of water quality in the lake due to financial and institutional constraints in the surrounding countries. A combination of satellite data and a semi-analytical algorithm can provide an alternative for routine monitoring of water quality, especially in developing countries. In this study, we first compared the performance of two semi-analytical algorithms, Doron11 and Lee15, which can estimate Secchi disk depth (SD) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…Similar to study results, Sitoki et al [38], Tran et al [45], reported the SD range value of 0.8-1.7 m (Lake Kyoga) and 0.17-2.3 m (Edward), respectively. On the other hand, Stoyneva-Gärtner et al [40], Vundo et al [49] and Ozguven & Demir Yetis [32] reported an SD range significantly higher than the recorded values in the present study.…”
Section: Variability In Physical Water Quality Parameterscontrasting
confidence: 75%
“…Similar to study results, Sitoki et al [38], Tran et al [45], reported the SD range value of 0.8-1.7 m (Lake Kyoga) and 0.17-2.3 m (Edward), respectively. On the other hand, Stoyneva-Gärtner et al [40], Vundo et al [49] and Ozguven & Demir Yetis [32] reported an SD range significantly higher than the recorded values in the present study.…”
Section: Variability In Physical Water Quality Parameterscontrasting
confidence: 75%
“…The independent validation dataset showed the distribution of the measured and estimated SDD along the 1:1 line, with the mean relative error and normalized root mean square error of 34% and 55%, respectively, indicating that the power function model based on the red band of Landsat reflectance was suitable for estimating the SDD of China's lakes covering SDD from <0.1 m to more than 10 m. Detailed information about the calibration, validation, and assessment of the model is provided in our previous study [36]. Overall, the precision of the SDD estimation model in our study was acceptable compared to similar previous studies [22][23][24][25].…”
Section: Remote Sensing Estimation Of Sdd Before 1995 and After 2005supporting
confidence: 55%
“…In the past few decades, remote sensing is considered an important supplement or substitute to obtain an overview of the temporal-spatial patterns of SDD due to its unparalleled advantages of collecting measurements from historical and large-scale perspectives [21]. Many arduous efforts have attempted to develop a series of empirical, semi-empirical, and semi-analytical algorithms to estimate SDD and explore the longterm changes in different inland waters using Landsat, MERIS, MODIS, and other images [20,[22][23][24][25]. A decrease in water clarity is associated with a reduced water quality, the loss of macrophytes and benthic algae, a decrease in primary production, decreases in habitat and fishery production, biodiversity loss, and a decrease in recreational value [13,18,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Since previous studies have confirmed that semianalytical Equations ( 2) and (3) are robust in waters with different optical properties if accurate a(λ) and b b (λ) are provided (e.g., [4,21,22,36,41]), our efforts were focused on how to obtain more accurate a(λ) and b b (λ) values from R rs (λ) spectra. A flowchart of the developed Z SD estimation algorithm is shown in Figure 2.…”
Section: Development Of a New Z Sd Estimation Algorithmmentioning
confidence: 99%